2018
DOI: 10.1159/000489808
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Against Hypoxic/Ischemic Injury: δ-Opioid Receptors and BDNF-TrkB Pathway

Abstract: The delta-opioid receptor (DOR) is one of three classic opioid receptors in the opioid system. It was traditionally thought to be primarily involved in modulating the transmission of messages along pain signaling pathway. Although there were scattered studies on its other neural functions, inconsistent results and contradicting conclusions were found in past literatures, especially in terms of DOR’s role in a hypoxic/ischemic brain. Taking inspiration from the finding that the turtle brain exhibits a higher DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Delta-opioid receptor (DOR) is a member of the opioid receptor superfamily and is widely expressed throughout the CNS (Chao and Xia 2015). Endogenous and exogenous DOR activation regulates a variety of signalling pathways, including the protein kinase A (PKA), mitogen-activated protein kinase (MAPK), protein kinase C (PKC), and brainderived neurotrophic factor (BDNF)/tropomyosin-related kinase B (TrkB) pathways to exert diverse effects, such as antinociceptive, antidepressant, and neuroprotective effects (Chu Sin Chung and Kieffer 2013;Sheng et al 2018). More importantly, a growing body of evidence has shown that the neuroprotective effect of DOR activation is related to MAPK signalling during ischaemia/hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Delta-opioid receptor (DOR) is a member of the opioid receptor superfamily and is widely expressed throughout the CNS (Chao and Xia 2015). Endogenous and exogenous DOR activation regulates a variety of signalling pathways, including the protein kinase A (PKA), mitogen-activated protein kinase (MAPK), protein kinase C (PKC), and brainderived neurotrophic factor (BDNF)/tropomyosin-related kinase B (TrkB) pathways to exert diverse effects, such as antinociceptive, antidepressant, and neuroprotective effects (Chu Sin Chung and Kieffer 2013;Sheng et al 2018). More importantly, a growing body of evidence has shown that the neuroprotective effect of DOR activation is related to MAPK signalling during ischaemia/hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…We further explored the putative signaling pathway involved in GBE-mediated neuroprotection. BDNF is well known to promote cell survival and neuroprotection in control conditions as well as in different pathological conditions ( Sheng et al, 2018 ). A study by Kramár et al showed that BDNF decreases the SK2 component by phosphorylation, causes its inactivation, and strengthens synaptic transmission ( Kramar et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, cancer patients undergoing intensive morphine treatment have an increased risk of stroke incidence [34]. Accordingly, a growing body of evidence has revealed the neuroprotective effects of the nonselective opioid receptor antagonist naloxone, δ opioid receptor agonists, and κ opioid receptor agonists in rodent models experiencing neurodegeneration [3,7,[9][10][11][24][25][26][35][36][37]. Being a CNS-penetrating compound, the selective µ opioid receptor antagonist β-funaltrexamine is capable of inhibiting LPS-induced neuroinflammation in mice after receiving an intraperitoneal injection [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its effect on the nociceptive/analgesic systems, the opioidergic system also displays effects on physiological and behavioral functions, including respiration, ion channel activity, and immune responses [1,2]. Additionally, alteration in the opioidergic system has been reported in the disease initiation and progression of several acute and chronic diseases, including neurodegenerative diseases [3][4][5][6][7][8][9]. These phenomena highlight the potential pathogenic roles that the opioidergic system may have and candidate targets for intervention with an aim to prevent and/or treat diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation